ANALISA EKONOMI PENGEMBANGAN KOMODITAS BAWANG MERAH DI KABUPATEN PADANG LAWAS UTARA - Shabil Hidayat; M.A Girsang; Sarman P. Tobing; Palmarum Nainggolan; Lermansius Haloho (Agric, 2020)
There are still many problems faced by shallot farmers in North Padang Lawas district, as horticultural farmers in other areas in Indonesia, become an obstacle in efforts to develop shallot commodities in North Padang Lawas Regency, so that it has not been able to provide optimal welfare to farmers. Although this commodity has traditionally been cultivated by farmers in several sub-districts within this district and The Ministry of Agriculture of the Republic of Indonesia has also designated North Padang Lawas Regency as one of the Development of National Shallot Commodity Agricultural Areas through Keputusan Menteri Pertanian Nomor 472 Tahun 2018 Regarding the National Agricultural Area, but it needs to be studied further to analyze the potential and economic development strategy of shallots as the aim of this study. This study was conducted from June to November 2019. The method used was a survey, followed by direct observation about the development of shallots in 6 (six) districts, interview with field extension officers, retailers and wholesalers in North Padang Lawas Regency. Data and information were analyzed descriptively and analyzed by R / C ratio. The results of the study show that shallot farming activities in North Padang Lawas Regency are very economically and financially feasible, with an ideal R / C ratio of 2.04 with a profit of Rp.76.108.500,- for each hectare of land cultivated for shallot cultivation.